(untitled) (The Journal of Psychology and Sociology, 2024)
The actuality of the problem of professional preference defining and studying of high school students is increasing. This is due to the fact that the successfulness of a professional orientation work in schools is one of the important indicators of modernization of Kazakhstani education as a guarantee of future youth employment and competitive positions in labour market. Given article is devoted to the studying the professional preferences of urban and rural high school students. The aim of the research is determining factors, similarities and differences that affecting on professional preferences of urban and rural high school students. In theoretical part of the given article was made an overview of scientific conceptions of professional preferences of high school students. The empirical part shows the results of the research conducted by questionnaire method among students (N=270) of urban and rural high school students (Almaty city and Almaty region). The results of the research demonstrate that students of urban high schools apply independently career guidance and counselling institutions outside of school, as well as rural youth prefer only school career guidance activities. Psychological testing is the widely used form of professional orientation work in urban and rural schools. The main factors which were affected by changes in the professional preferences of urban youth are the demand for particular specialities in the labour market, as well as on students of rural schools affect of social ties. Rural youth don’t have a concrete position in choosing not only a profession, also a higher educational institution. The high level of remuneration is very important in future job as urban as rural youth. The results of the study can be used to develop recommendations and further improve the effectiveness of vocational guidance for young people in the education system. Key words: profession, professional preferences, choice of profession, career guidance, schoolchildren, rural youth, urban youth.